Screening large-scale association study data: exploiting multi-gene interactions with random forests - Lunetta, Kathryn (Henry Stewart Talks, 2007)
Screening association studies with a two-stage approach, Multiplicative models with heterogeneity, Random forest analysis, Random forest variable importance, Power, Effect of linkage disequilibrium, Genome-wide association studies, Computational issues
Archived at 2021/02/25